1999
DOI: 10.1088/0022-3727/32/10a/313
|View full text |Cite
|
Sign up to set email alerts
|

High resolution x-ray diffraction analyses of GaN/LiGaO2

Abstract: Lithium gallate (LiGaO2) is gaining increasing attention as a potential substrate for the growth of the important semiconductor GaN. In order to better understand this material we have performed high-resolution double- and triple-axis x-ray diffraction analyses of both the starting LiGaO2 and GaN/LiGaO2 following epitaxial growth. A high-resolution triple-axis reciprocal space map of the substrate showed a sharp, well-defined crystal truncation rod and a symmetric streak of intensity perpendicular to q002, sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…The orientation relationship between the hexagonal GaN layer and orthorhombic LGO is (0001) GaN || (001) LGO and [ ] 1210 GaN || [010]LGO. This observation confirms the relationship examined by Matyi et al 7 Figure 4a is a cross-sectional HRTEM image displaying the interface between GaN and LGO. Typically, low dislocation density material grown by MOCVD is produced by nucleating small crystallites, often of cubic structure.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The orientation relationship between the hexagonal GaN layer and orthorhombic LGO is (0001) GaN || (001) LGO and [ ] 1210 GaN || [010]LGO. This observation confirms the relationship examined by Matyi et al 7 Figure 4a is a cross-sectional HRTEM image displaying the interface between GaN and LGO. Typically, low dislocation density material grown by MOCVD is produced by nucleating small crystallites, often of cubic structure.…”
Section: Resultssupporting
confidence: 91%
“…Additionally, AlGaN can be lattice matched to LGO at growth temperature or room temperature by appropriate selection of Al composition. [3][4][5][6][7][8][9] Employing LGO as a substrate, we recently reported the electrical characteristics of the first demonstration of a twodimensional electron gas (2DEG) produced at an AlGaN/GaN heterostructure on LGO. The electron mobility was 731 cm 2 /Vs and sheet electron concentration was 1.3 × 10 13 cm -2 at room temperature measured on 1 cm × 1 cm sample without any patterning performed on the sample.…”
Section: Characterization Of Algan/gan Structures On Various Substratmentioning
confidence: 99%
“…One such substrate, lithium gallate (LGO), LiGaO 2 , has been the focus of much interest in recent years. Our results [9][10][11][12][13][14] have shown that the structural quality, as determined by x-ray diffraction, is very good. We have also, recently, been able to demonstrate device-quality electrical properties.…”
Section: Abstract: Gan Growth Ligao 2 Substratesmentioning
confidence: 85%
“…This asymmetry leads to a slight, in plane rotation on the order of 3 degrees about the c-axis. 13 No mosaic structure results from this pure rotation. Al can be added to the GaN to equalize the magnitude of the a and b axis mismatch.…”
Section: Abstract: Gan Growth Ligao 2 Substratesmentioning
confidence: 97%
See 1 more Smart Citation